THE EFFECT OF SUBSIDIARY OWNERSHIP, LEVERAGE, AND CAPITAL INTENSITY ON TAX AVOIDANCE: PROFITABILITY’S MODERATING ROLE: An empirical study of manufacturing companies listed on the IDX in 2023 - Nadia Annisa; Chandra Situmeang (Program Studi Magister Manajemen Universitas Advent Indonesia, 2025)
Taxes are the largest source of state revenue used to finance the national budget. Indonesia's tax ratio in 2024 was only 10.2 percent, reflecting relatively low tax revenue. This study aims to examine the effects of subsidiary ownership, leverage, and capital intensity on tax avoidance, as well as the moderating role of profitability in these relationships. The population of this study comprises 165 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2023, from which 141 samples were selected using a purposive sampling method. The research employed secondary data obtained from financial statements available on the IDX website (www.idx.co.id). The results indicate that subsidiary ownership, leverage, and capital intensity do not significantly affect tax avoidance. Furthermore, profitability does not moderate the relationship between subsidiary ownership, leverage, and capital intensity with tax avoidance.